2013
DOI: 10.1007/s00431-013-2092-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D fortification of growing up milk prevents decrease of serum 25-hydroxyvitamin D concentrations during winter: a clinical intervention study in Germany

Abstract: Vitamin D plays an important role in human health. Current recommendations for vitamin D intake and endogenous supply through sun exposure are not met in German pre-school children, and suboptimal serum 25-hydroxyvitamin D concentrations, especially during the winter months, are common. Consequently, vitamin D supplementation or fortification have gained increased acceptance. The KiMi trial (Kindermilch=growing up milk) was a prospective, randomized, and double-blind study in which young children (2-6 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 25 publications
2
55
0
5
Order By: Relevance
“…EAR or UL), which would otherwise be overestimated. Although vitamin D and iron status measures were not available from the NPNS, in many other populations, it has been shown that the approaches suggested in the present study can effectively improve vitamin D and iron status in young children . Misreporting or under‐reporting of energy intake are known limitations with all dietary assessments; this issue was minimised by a high‐level of researcher–participant interaction by trained nutritionists.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…EAR or UL), which would otherwise be overestimated. Although vitamin D and iron status measures were not available from the NPNS, in many other populations, it has been shown that the approaches suggested in the present study can effectively improve vitamin D and iron status in young children . Misreporting or under‐reporting of energy intake are known limitations with all dietary assessments; this issue was minimised by a high‐level of researcher–participant interaction by trained nutritionists.…”
Section: Discussionmentioning
confidence: 94%
“…Fortified foods and supplements can represent an opportunity to improve intakes and adequacy of vitamin D and iron in all population groups (14)(15)(16)(17)(18)(19)(20) . The practical and theoretical impacts of vitamin D fortification of dairy products have been widely investigated, demonstrating that it is an effective strategy for increasing dietary intake and serum 25-hydroxyvitamin D (25(OH)D) concentrations in many population groups (21)(22)(23)(24)(25)(26) .…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of serum 25(OH)D was only possible for those subjects with sufficient amounts of blood available, resulting in a small sample size. Analyses on parameters that have been used to complement 25(OH)D levels and/or used as blood safety measurements in other studies [34,35], such as parathyroid hormone, serum calcium, alkaline phosphatase and C-reactive protein, were not performed. There is a possibility that the method used for quantitative analyses of serum 25(OH)D may overestimate the 25(OH)D concentration in infants, due to the possible presence of C -3 epimers [36,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Положительные эффекты применения «третьих фор-мул» у детей старше 1 года отражены в результатах неко-торых современных исследований [5][6][7][8][9][10].…”
unclassified
“…В 2013 г. опубликованы данные проспективного рандомизированного двойного слепого исследования, в котором 92 ребенка в возрасте 2-6 лет получали либо сухую молочную смесь для детей старше 12 мес, содер- ежедневное потребление «третьей формулы», обога-щенной витамином D, в летние месяцы было безопас-ным, поскольку не вызывало повышения концентрации 25(OH)D в сыворотке крови, несмотря на актив-ный эндогенный синтез витамина D в летние месяцы [5]. Сравнительное исследование потребления основных пищевых веществ и энергии в двух группах детей в воз-расте 1-2 лет во Франции, получавших коровье молоко или «третью формулу», показало, что прием обогащенной смеси значительно снижает риск недостаточности желе-за и витамина D, так же как и ␣-линоленовой кислоты и витамина С [6].…”
unclassified